Implementing Open Educational Resource to Strengthen English Speaking Skills - Widia Yunita; Havid Ardi (Universitas Pendidikan Mandalika, 2022)
The purpose of this study was to analyze the improvement of English speaking skills from the application of Open Educational Resource (OER). The research method uses Exploratory Mixed Method. Qualitative data was taken during the observation process, while quantitative data was taken from the results of the pre-test and post-test. The participants were 4th-semester students who took the Speaking 2 course. The number of students who participated was 60 people. Qualitative data were analyzed through the data reduction stage, then the data presentation, and the conclusion stage. Meanwhile, the data on the results of the practice and the English-speaking test were presented in the form of descriptive statistics and t-tests. The results showed that OER had a positive impact on improving English speaking skills. This can be understood from the diversity of OER types used during the learning process. The results of the study have implications for the understanding of educators related to the provision of learning resources that are to the needs of students and current technological developments so that learning activities are relevant to the changes and needs of 21st-century educational competencies.